Cavitation energies can outperform dispersion interactions - He, Suhang; Biedermann, Frank; Vankova, Nina; Zhechkov, Lyuben; Heine, Thomas; Hoffman, Roy E.; De Simone, Alfonso; Duignan, Timothy T.; Nau, Werner M. (Nature chemistry, 2018)
The accurate dissection of binding energies into their microscopic components is challenging, especially in solution. Here we study the binding of noble gases (He–Xe) with the macrocyclic receptor cucurbit[5]uril in water by displacement of methane and ethane as 1 H NMR probes. We dissect the hydration free energies of the noble gases into an attractive dispersive component and a repulsive one for formation of a cavity in water. This allows us to identify the contributions to host–guest binding and to conclude that the binding process is driven by differential cavitation energies rather than dispersion interactions. The free energy required to create a cavity to accept the noble gas inside the cucurbit[5]uril is much lower than that to create a similarly sized cavity in bulk water. The recovery of the latter cavitation energy drives the overall process, which has implications for the refinement of gas-storage materials and the understanding of biological receptors.
CRIS-Team Scopus Importer:2022-04-14